2009
DOI: 10.1210/jc.2008-1695
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Gonadotropins and Estradiol in Premenopausal Women by Oral Administration of the Nonpeptide Gonadotropin-Releasing Hormone Antagonist Elagolix

Abstract: Oral administration of a nonpeptide GnRH antagonist, elagolix, suppressed the reproductive endocrine axis in healthy premenopausal women. These results suggest that elagolix may enable dose-related pituitary and gonadal suppression in premenopausal women as part of treatment strategies for reproductive hormone-dependent disease states.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(81 citation statements)
references
References 26 publications
5
75
0
1
Order By: Relevance
“…Consistent with the phase 1 hormone data in healthy premenopausal women (17), administration of elagolix resulted in dosedependent reductions in serum E 2 concentrations, with 200 mg BID and 300 mg BID resulting in median E 2 concentrations of 11 pg/mL through month 2 (Supplemental Table 9). With add-back therapies, numerically higher E 2 concentrations were observed, with median E 2 concentrations of 22 to 23 and 42 pg/mL, respectively, for the elagolix 200 mg BID plus low-dose E 2 / NETA and elagolix 300 mg BID plus E 2 /cyclical EP groups.…”
Section: Estradiol Concentrationssupporting
confidence: 70%
See 1 more Smart Citation
“…Consistent with the phase 1 hormone data in healthy premenopausal women (17), administration of elagolix resulted in dosedependent reductions in serum E 2 concentrations, with 200 mg BID and 300 mg BID resulting in median E 2 concentrations of 11 pg/mL through month 2 (Supplemental Table 9). With add-back therapies, numerically higher E 2 concentrations were observed, with median E 2 concentrations of 22 to 23 and 42 pg/mL, respectively, for the elagolix 200 mg BID plus low-dose E 2 / NETA and elagolix 300 mg BID plus E 2 /cyclical EP groups.…”
Section: Estradiol Concentrationssupporting
confidence: 70%
“…Elagolix is an oral, nonpeptide GnRH antagonist that suppresses the pituitary-ovarian axis in a dose-dependent manner, with partial suppression at lower doses and nearly full suppression at higher doses in previous phase 1 (17) and phase 2 research (18). Phase 2 studies in women with endometriosis-associated pain demonstrated the efficacy of elagolix in reducing pain symptoms, with an acceptable safety and tolerability profile (19)(20)(21)(22).…”
mentioning
confidence: 99%
“…Although the pathogenesis of endometriosis and associated pain and infertility remains incompletely understood, therapies aimed at correcting progesterone resistance (e.g., selective progesterone-receptor modulators) and systemic immune dysfunction, as well as those targeting angiogenesis, inflammation, neurotropism, and pain transmission, including a neuropathic component, warrant further study. Oral GnRH antagonists and other small molecules that suppress circulating estradiol levels to the range suggested by the estrogen threshold hypothesis (30 to 45 pg per milliliter) 49 also warrant investigation. Studies of complementary or alternative therapies are needed.…”
Section: Areas Of Uncertaintymentioning
confidence: 99%
“…These properties suggest that elagolix may enable doserelated pituitary and gonadal suppression in premenopausal women as part of treatment strategies for reproductive hormone-dependent disease states. 93…”
Section: Promising Gnrh Antagonist (Elagolix)mentioning
confidence: 99%